Coal liquefaction pitch refining method and application of coal liquefaction pitch in anode material
Through solvent extraction, centrifugal separation and continuous sedimentation or filtration, coal liquefied asphalt is refined, which solves the problems of its high solids content and ash content, and high-performance refined asphalt is prepared, which is used as a binder for anode materials, significantly improving the performance and production efficiency of carbon products.
Patent Information
- Application Number
- CN202510004744.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
The application of coal liquefied asphalt in the carbon industry is limited by its high solids content and ash content, resulting in low strength, high additional losses, and low efficiency, high cost or unstable effect of carbon products.
Through solvent extraction, centrifugation and continuous sedimentation or filtration, coal liquefied asphalt is refined to remove its solid content and ash, and refined asphalt has high softening points, good adhesion, high coking value and low QI value are prepared, and it is used as a binder for anode material.
It realizes efficient refining of coal liquefied asphalt, improving the production efficiency and performance of anode materials, including high volume density, high pressure resistance, low resistivity and low permeability.
Smart Images

Figure BDA0005226524190000071 
Figure BDA0005226524190000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of asphalt deep processing, and in particular to a coal liquefaction asphalt refining method and application thereof in anode materials. Background Art
[0002] Coal liquefaction pitch (DCLR) is a byproduct of the coal liquefaction process. It comes from the coal conversion process under high temperature, high pressure and hydrogenation conditions. It is rich in organic components such as polycyclic aromatic hydrocarbons, but also contains a high solid content (such as ash, catalyst residues, etc.) and insoluble substances, accounting for about 30% of the total amount of raw coal. Due to its unique chemical composition, coal liquefaction pitch has been initially applied in the fields of coal blending, coking, waterproofing membranes and activated carbon binders.
[0003] However, in existing applications, the high solid content and ash content of coal liquefaction pitch limit its potential for use as a high-end product, especially in areas with high performance requirements such as the carbon industry. Traditionally, the carbon industry relies on modified asphalt as a binder, but the production process of modified asphalt is complex and costly, and there are problems such as high QI value, low coking value, and high ash content, resulting in low strength of carbon products, more additional losses, and average overall product performance. Therefore, how to remove the solid content and ash content of coal liquefaction pitch and achieve its efficient utilization has become the key to improving the economic benefits of direct coal liquefaction projects and promoting the green development of the carbon industry.
[0004] In response to the above problems, various treatment technologies have been explored in the field, such as solvent extraction, filtration and centrifugation, aiming to reduce the impurity content in coal liquefaction asphalt. However, these methods still have the disadvantages of low treatment efficiency, high cost or unstable effect in practical applications, and it is difficult to fully meet the production needs of high-quality binders. Summary of the invention
[0005] The purpose of the present invention is to solve the problems raised in the background technology and to provide a method for refining coal liquefaction pitch and its application in anode materials.
[0006] In order to achieve the above object, the first aspect of the present invention provides a method for refining coal liquefaction pitch, comprising the following steps:
[0007] (S1) mixing an extraction solvent with coal liquefaction asphalt to form a mixture;
[0008] (S2) centrifuging the mixture to obtain a centrifugal clear liquid and a centrifugal dry phase;
[0009] (S3) After heating the centrifuged clear liquid, performing continuous sedimentation separation or filtration operation, if sedimentation separation is performed, a sedimentation clear liquid and a sedimentation bottom liquid are obtained; if filtration operation is performed, a filtered clear liquid and a filtered residue are obtained;
[0010] (S4) distilling the sedimentation supernatant or the filtered supernatant to obtain refined asphalt.
[0011] The second aspect of the present invention provides a use of the asphalt obtained by the above refining method as a binder for anode materials.
[0012] A third aspect of the present invention provides a method for preparing an anode carbon block, comprising the following steps:
[0013] (R1) preheating the petroleum coke to obtain a pretreated material;
[0014] (R2) kneading the pretreated material with the refined asphalt to obtain a kneaded material;
[0015] (R3) extruding the mixed material to obtain a green material;
[0016] (R4) The green material is calcined and then cooled to obtain an anode material.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The present invention can shorten the sedimentation time of coal liquefaction pitch and reduce the solid content (insoluble matter such as tetrahydrofuran and minerals such as catalysts) in coal liquefaction pitch by subjecting coal liquefaction pitch to solvent extraction, centrifugal separation and continuous sedimentation (or filtration), thereby ultimately achieving the refining of coal liquefaction pitch.
[0019] 2. The refined asphalt provided by the present invention has the advantages of high softening point, good adhesion, high coking value, good high-temperature fluidity, low QI value, etc. It can be directly used as a binder for anode materials, eliminating the steps of asphalt modification, thereby improving the production efficiency of anode materials and reducing costs.
[0020] 3. The present invention uses a simple method to prepare anode materials, which is obtained by mixing, kneading, molding and roasting petroleum coke and the refined asphalt of the present invention. The refined asphalt can well infiltrate petroleum coke aggregate and promote the formation of a carbon grid structure. The obtained anode material has the advantages of high volume density, high compressive strength, low resistivity and low permeability. DETAILED DESCRIPTION
[0021] The present invention is further described below, but is not limited to the following embodiments. Changes made by ordinary technicians in this field based on the embodiments are still within the scope of protection of this patent.
[0022] The first aspect of the present invention provides a method for refining coal liquefaction pitch, comprising the following steps:
[0023] (S1) mixing an extraction solvent with coal liquefaction asphalt to form a mixture;
[0024] (S2) centrifuging the mixture to obtain a centrifugal clear liquid and a centrifugal dry phase;
[0025] (S3) After heating the centrifuged clear liquid, performing a sedimentation separation or filtering operation, if sedimentation separation is performed, a sedimentation clear liquid and a sedimentation bottom liquid are obtained; if filtering operation is performed, a filtered clear liquid and a filtered residue are obtained;
[0026] (S4) distilling the sedimentation supernatant or the filtered supernatant to obtain refined asphalt.
[0027] In the present invention, the coal liquefaction asphalt is the coal liquefaction asphalt specified in the national standard GB / T 38772-2020, and its softening point is 140-200°C, and the ash content is ≤25wt%.
[0028] In step (S1), an extraction solvent is mixed with coal liquefaction asphalt to extract asphaltene in the coal liquefaction asphalt; in some embodiments, the extraction solvent is selected from at least one of toluene, coal liquefaction oil with a distillation range of 150-260°C, or wash oil.
[0029] Furthermore, the extraction solvent is preferably wash oil.
[0030] In some embodiments, in the mixture of step (S1), the mass ratio of the extraction solvent to the coal liquefaction asphalt is (1-8):1, preferably (3-5):1.
[0031] Furthermore, the mixing is performed at a temperature of 90-150°C.
[0032] Furthermore, the extraction rate of the coal liquefaction pitch is 38-57%, and the extraction rate refers to the yield of the obtained refined pitch relative to the raw material (coal liquefaction pitch).
[0033] In some embodiments, in step (S2), the mixture is stirred and then separated in a horizontal screw centrifuge and / or a vertical centrifuge in the art to obtain a centrifugal clear liquid with a lower ash content and a centrifugal dry phase with a higher solid content; wherein the extraction solvent in the centrifugal dry phase is recovered in, for example, a spray drying tower.
[0034] Furthermore, the centrifugal separation temperature is 90-130°C.
[0035] Furthermore, the ash content of the centrifuged clear liquid is ≤5wt%, and the solid content of the centrifuged dry phase is ≥30wt%.
[0036] In step (S3), the centrifugal supernatant is heated to a temperature of 90-130° C. to reduce the viscosity of the centrifugal supernatant, and then enters the continuous sedimentation separation tank, ultimately improving the efficiency of the continuous sedimentation separation or filtration operation.
[0037] In some embodiments, the centrifugal clear liquid is heated and then subjected to sedimentation separation, specifically: the centrifugal clear liquid is heated and then pumped into a continuous sedimentation tank to continuously remove a small amount of solid content therein; wherein, after the centrifugal clear liquid stays in the sedimentation tank for a certain period of time, a sedimentation clear liquid with low impurities (i.e., low ash content) continuously overflows from the top of the sedimentation tank, and a sedimentation bottom liquid with a high solid content is discharged from the bottom of the sedimentation tank. The solvent in the sedimentation bottom liquid is recovered in, for example, a spray drying tower.
[0038] Furthermore, the ash content of the sedimentation clear liquid is ≤0.3wt%, and the solid content of the sedimentation bottom liquid is ≥2wt%.
[0039] In step (S4), the sedimentation clear liquid or the filtered clear liquid is distilled to remove the extraction solvent therein, and the refined coal liquefaction pitch (i.e., refined pitch) can be obtained, which has a high softening point, a high coking value, and a low QI value. In some embodiments, the distillation can be atmospheric distillation or vacuum distillation to remove the extraction solvent.
[0040] In some embodiments, the refined asphalt has many advantages as a binder asphalt. Its high coking value significantly improves the strength of carbon products; its low ash content reduces the extra loss of carbon products; its low QI value promotes good wetting and penetration of the binder and aggregate, thereby enhancing the density and strength of the product; and its suitable softening point can match the kneading process requirements of carbon products, effectively reducing production energy consumption.
[0041] Furthermore, the refined asphalt has a coking value of 50-62.3wt%, an ash content of 0.01-0.1wt%, a QI value of 0.3-1.2wt%, and a softening point of 103-156°C.
[0042] The second aspect of the present invention provides a use of the asphalt obtained by the above refining method as a binder for anode materials.
[0043] A third aspect of the present invention provides a method for preparing an anode material, comprising the following steps:
[0044] (R1) preheating the petroleum coke to obtain a pretreated material;
[0045] (R2) kneading the pretreated material with the refined asphalt to obtain a kneaded material;
[0046] (R3) extruding the mixed material to obtain a green material;
[0047] (R4) The green material is calcined and then cooled to obtain an anode material.
[0048] In step (R1), the petroleum coke is the petroleum coke specified in the industry standard NB / SH / T 0527-2019, and the quality standard is 2C or above; the petroleum coke includes at least one of calcined petroleum coke, residual anode, and coke powder return material, containing large particles with a particle size of 6-9 mm and fine powder with a particle size of less than 200 mesh, and the ratio of large particles to fine powder can be (1-3):1.
[0049] In some embodiments, the petroleum coke is pretreated before the preheat treatment, including processes such as secondary crushing, screening, grinding, dry mixing, etc., to ensure the uniformity of the petroleum coke.
[0050] In step (R1), the preheating treatment heats the petroleum coke to a certain temperature to reduce the thermal stress during the roasting process and improve the oxidation resistance of the anode material. In some embodiments, the preheating treatment time is 30-40 minutes; the preheating treatment temperature is 160-200°C, preferably 180-190°C, and more preferably 185°C.
[0051] The inventors have found that the appropriate preheating temperature can improve the wettability of refined asphalt (i.e., binder asphalt) to petroleum coke (i.e., aggregate). When the preheating temperature is too low, the viscosity of the binder asphalt increases, which will reduce the uniform mixing with the aggregate; when the preheating temperature is too high, although the wettability of the binder asphalt can be increased, the higher temperature increases energy consumption and also causes volatilization loss of the binder asphalt.
[0052] In step (R2), the pretreated material and the refined asphalt are fully kneaded to form a paste-like kneaded material, which is then heated to standby. In some embodiments, the kneading time is 30-40 minutes; the kneading temperature is 170-230°C, preferably 200-225°C, and more preferably 220°C.
[0053] The inventors have found that the temperature of the kneading treatment is the key to the impregnation of the binder asphalt into the petroleum coke. Although a higher temperature can increase the penetration of the binder asphalt into the aggregate, it will also increase the energy consumption of the subsequent steps. At a lower kneading temperature, the binder asphalt is difficult to penetrate into the aggregate, resulting in low compressive strength of the anode material obtained after calcination.
[0054] In step (R2), during the kneading, the amount of the refined asphalt added is 10-20wt% of the kneaded material, preferably 14-17wt%, more preferably 15wt%.
[0055] The inventors have found that the amount of refined asphalt (i.e., binder asphalt) added has a significant impact on the quality of the anode material. When the binder asphalt content is low, the dispersion of asphalt and petroleum coke is poor, and it is difficult to form a dense carbon grid structure after kneading, resulting in a high resistivity of the anode material; when the binder asphalt content is high, more weight loss will occur after calcination, ultimately resulting in the compressive strength of the obtained anode material not meeting the requirements.
[0056] In step (R3), the kneaded material is extruded to prepare a shaped green body that meets industrial use, i.e., a green body material. In some embodiments, the extrusion molding pressure is 40-70 kg / cm 2 , time is 1-5min. In some embodiments, vibration molding can also be used instead of extrusion molding.
[0057] In some embodiments, in step (R4), the green material is cooled to 40-50°C and then calcined under the protection of an inert gas (e.g., nitrogen) to remove volatile components in the refined asphalt and leave a dense carbonaceous grid structure; the residual dust adhering to the surface of the calcined product is then cleaned to ensure product quality, and finally cooled to ambient temperature (e.g., 10-50°C) to obtain the anode material.
[0058] Furthermore, the calcination treatment is carried out at a temperature of 1100-1200° C. and for a time of 18-22 hours.
[0059] In some embodiments, the anode material exhibits the following excellent properties: the volume density is maintained at 1.51-1.61 g / cm 3 The range of 2.0-3.0mm can effectively reduce air infiltration and extend the service life of the electrolytic cell. The compressive strength is as high as 22.3-25.4MPa, ensuring stability during the treatment process. The resistivity is as low as 61-79μΩ·m, which significantly reduces the electrolytic cell voltage and improves the energy efficiency of electrolytic aluminum. At the same time, the permeability is controlled between 2.1-5.7npm, which reasonably balances the gas permeability and the net consumption of anode materials.
[0060] The present invention will be further described in detail below through specific examples. In the following examples and comparative examples:
[0061] The coal liquefaction asphalt comes from Ordos Coal to Oil Company, has a softening point of 182° C., and an ash content of 15.7 wt %.
[0062] The petroleum coke comes from Sinopec Qilu Petrochemical Company, and its indicators meet the 2B requirements of the petroleum coke quality standard NB / SH / T0527-2019.
[0063] The modified asphalt comes from Shandong Jining Chenyang Carbon Co., Ltd., and has a softening point of 110.8°C, a coking value of 53.6wt%, an ash content of 0.2wt%, and a QI value of 6.47wt%. The modified asphalt can be used as a binder asphalt in this field.
[0064] The softening point is measured according to GB / T 30043.
[0065] The coking value is measured according to GB / T 8727.
[0066] The ash content is measured according to GB / T 29748.
[0067] The QI value is measured according to GB / T 2293.
[0068] The bulk density, compressive strength, resistivity and permeability are measured in accordance with the prebaked anode YS / T 285 standard.
[0069] The extraction rate refers to the yield of the refined asphalt obtained relative to the raw material (coal liquefaction pitch), that is, extraction rate (wt%) = refined asphalt / coal liquefaction pitch × 100%.
[0070] Example 1 (A1)
[0071] (S1) in a mixing tank, the extraction solvent and the coal liquefaction asphalt are fully stirred and mixed at 130° C. to form a mixture; wherein,
[0072] The extraction solvent is toluene;
[0073] The weight ratio of the extraction solvent to the coal liquefaction pitch is 3:1 (ie, the weight ratio of the solvent to the pitch).
[0074] (S2) In a horizontal screw centrifuge, the mixed material is centrifuged at 100° C. to obtain a centrifugal clear liquid and a centrifugal dry phase.
[0075] (S3) heating the centrifuged clear liquid to 130° C., and then pumping it into a continuous sedimentation tank for sedimentation separation, wherein the clear liquid overflows from the top of the sedimentation tank and the bottom liquid is discharged from the bottom of the sedimentation tank; wherein,
[0076] The sedimentation bottom liquid is mixed with the centrifugal dry phase in step (S2), and then spray-dried to achieve the recovery and utilization of the extraction solvent.
[0077] (S4) The sedimentation clear liquid is subjected to vacuum distillation at 350° C. and 5 kPa to obtain refined asphalt; wherein the extraction rate and various characterizations of the refined asphalt are given in the following Table 1.
[0078] Example 2-Example 6 (A2-A6)
[0079] Refer to Example 1, the only difference is:
[0080] In step (S1), the weight ratio of solvent / asphalt is different depending on the type of extraction solvent, as shown in Table 1.
[0081] Table 1:
[0082]
[0083] From Table 1, we can see that:
[0084] Compared with the modified asphalt prepared from conventional coal tar pitch (Comparative Example 1), the refined asphalt of the present invention (except Example 1) exhibits significantly improved performance: higher softening point and coking value, accompanied by lower ash content and QI value. It is particularly pointed out that whenever toluene is selected as the extraction solvent, although its extraction effect is slightly insufficient, resulting in its softening point and coking value being slightly inferior to the modified asphalt in the art, it is effective in reducing ash content and QI value. This phenomenon may be attributed to the low asphaltene component in coal liquefaction asphalt, which affects the efficiency of toluene.
[0085] However, the situation is greatly improved when an aromatic-rich and high-distillation solvent is used as the extraction solvent. Wash oil significantly improves the extraction rate of coal liquefaction asphalt due to its excellent solubility, especially when the mass ratio is 3:1 to 4:1, the extraction rate exceeds 50%, and almost achieves the full extraction of asphaltene. The softening point of the refined asphalt obtained in this way jumps to above 150°C, the coking value exceeds 60wt%, and the QI value is as low as about 1wt%, and the ash content is strictly controlled below 0.1wt%. This excellent combination makes it particularly suitable as an ideal raw material for high-end applications such as graphite electrode binder or pre-baked anode for electrolytic aluminum.
[0086] The refined asphalt in Example 5 is used as binder asphalt in the subsequent preparation of anode materials due to its excellent performance.
[0087] Example 7 (A7)
[0088] (R1) preheating petroleum coke in a nitrogen atmosphere to obtain a pretreated material; wherein,
[0089] The temperature of the preheating treatment is 160°C.
[0090] (R2) kneading the pretreated material with the binder asphalt to obtain a paste-like kneaded material; wherein:
[0091] The binder asphalt is derived from the refined asphalt obtained in Example 5;
[0092] The amount of the binder asphalt added is 13wt% of the mixed material (ie the binder ratio is 13wt%).
[0093] The temperature of the kneading treatment is 220°C;
[0094] (R3) In an extrusion molding machine, at a pressure of 60 kg / cm 2 The mixed material is extruded under the conditions of 0.5 % and 1.5 % for 2 min to obtain a green material.
[0095] (R4) The green material is cooled to ambient temperature, and then calcined in a nitrogen atmosphere at 1100° C. for 22 h, and cooled to ambient temperature again to obtain an anode material. The characterization of the anode material is shown in Table 2 below.
[0096] Example 8-Example 13 (A8-A13)
[0097] Refer to Example 7, the only difference is:
[0098] As shown in Table 2, the preheating temperature of petroleum coke is different, the binder ratio is different, and the kneading temperature of the pretreated material is different.
[0099] Comparative Example 1
[0100] Refer to Example 7, the only difference is:
[0101] As shown in Table 2, the sources of binder asphalt are different, the binder ratio is different, and the kneading temperature of the pre-treated material is different;
[0102] The binder asphalt is modified asphalt, with a softening point of 103° C., a coking value of 50wt%, an ash content of 0.01wt%, and a QI value of 0.3wt%.
[0103] Comparative Example 2
[0104] Refer to Example 7, the only difference is:
[0105] As shown in Table 2, the sources of binder asphalt are different, the binder ratio is different, and the mixing temperature of the pretreated material is different.
[0106] Table 2:
[0107]
[0108] From Table 2, we can see that:
[0109] Compared with Comparative Example 1 (using modified asphalt) and Comparative Example 2 (using the refined asphalt in Example 1), which use binder asphalt with lower softening point and coking value, Examples 7-13 use the refined asphalt obtained in Example 5 as a binder, and the resulting anode materials have better comprehensive performance.
[0110] It can be seen from Examples 7-9 that, within the scope of the present invention, as the temperature of the preheating treatment of petroleum coke increases, the volume density of the anode material increases slightly, the compressive strength gradually increases, the resistivity gradually decreases, and the permeability increases slightly.
[0111] It can be seen from Examples 8, 11 and 13 that, within the scope of the present invention, as the amount of binder asphalt added increases, the volume density of the anode material first increases and then decreases, the compressive strength first increases and then decreases, the resistance first decreases and then increases, and the permeability first decreases and then increases.
[0112] It can be seen from Examples 10-12 that, within the scope of the present invention, as the temperature of the pretreated material during the kneading treatment increases, the volume density of the anode material first increases and then decreases, the compressive strength first increases and then decreases, the resistance first decreases and then increases, and the permeability first decreases and then increases.
[0113] In summary, in Example 11, the preheating temperature of the petroleum coke is 185°C, the amount of binder added (binder ratio) is 15wt%, and the kneading temperature is 220°C. The comprehensive performance (including volume density, compressive strength, resistivity, and permeability) of the anode product prepared under this condition is the best.
[0114] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A method for refining coal liquefaction pitch, characterized in that: The following steps are involved: (S1) mixing an extraction solvent with coal liquefaction asphalt to form a mixture; (S2) centrifuging the mixture to obtain a centrifugal clear liquid and a centrifugal dry phase; (S3) After heating the centrifuged clear liquid, performing continuous sedimentation separation or filtration operation, if sedimentation separation is performed, obtaining a sedimentation clear liquid and a sedimentation bottom liquid; If a filtration operation is performed, a filtration clear liquid and a filtration residue are obtained; (S4) distilling the sedimentation supernatant or the filtered supernatant to obtain refined asphalt.
2. The refining method according to claim 1, characterized in that In step (S1), the extraction solvent is selected from at least one of toluene, coal liquefaction oil with a distillation range of 150-260° C., or wash oil; Preferably, the extraction solvent is wash oil; The mass ratio of the extraction solvent to the coal liquefaction pitch is (1-8):1, preferably (3-5):
1.
3. The purification method according to claim 1 or 2, characterized in that: In step (S1), the mixing is carried out at a temperature of 90-150°C; In step (S2), the centrifugal separation temperature is 90-130°C; In step (S3), the temperature of the centrifuged supernatant after heating is 90-130°C.
4. The refining method according to any one of claims 1 to 3, characterized in that In step (S3), the centrifuged clear liquid is heated and then enters a continuous sedimentation separation tank to perform continuous sedimentation separation, and the sedimentation bottom liquid and the centrifuged dry phase are spray dried together to recover the extraction solvent.
5. Use of the asphalt obtained by the refining method according to any one of claims 1 to 4 as a binder for anode materials.
6. A method for preparing an anode material, characterized in that: The following steps are involved: (R1) preheating the petroleum coke to obtain a pretreated material; (R2) kneading the pretreated material with the refined asphalt obtained by the refining method according to any one of claims 1 to 4 to obtain a kneaded material; (R3) extruding the mixed material to obtain a green material; (R4) The green material is calcined and then cooled to obtain an anode material.
7. The preparation method according to claim 6, characterized in that: In step (R1), the temperature of the preheat treatment is 160-200°C.
8. The preparation method according to claim 6 or 7, characterized in that: In step (R2), the kneading temperature is 170-230°C. During the kneading, the amount of the refined asphalt added is 10-20wt% of the kneaded material.
9. The preparation method according to any one of claims 6 to 8, characterized in that: In step (R3), the extrusion pressure is 40-70 kg / cm 2 , time is 1-5min.
10. The preparation method according to any one of claims 6 to 9, characterized in that: In step (R4), the calcination treatment is carried out under the protection of an inert gas; The calcination treatment is carried out at a temperature of 1100-1200° C. and for a time of 18-22 hours.